Green light triggered [2+2] cycloaddition of halochromic styrylquinoxaline—controlling photoreactivity by pH - Kubra Kalayci (Nature Portfolio, 2020)
Light gated reactions are important due to their spatial and temporal control over the chemical processes but long wavelength activation of photocycloaddition reactions are rare. Here the authors introduce a green light induced [2+2] cycloaddition of a halochromic system, which allows for its photo-reactivity to be switched on and off by adjusting the pH of the system.